Behavior, mechanism, and equilibrium studies of rhodium(i) extraction from hydrochloric acid with HMImT. (16th August 2017) - Yin, Xiaolu; Wang, Qi; Wang, Shubin; Zhang, Hong; Guo, Jinxin; Yang, Yanzhao
Abstract : An efficient and low-viscosity extractant (1-hexyl-3-methylimidazole-2-thione) was firstly synthesized and used to extract Rh(i ) from multimetal ion solution. Abstract : 1-Hexyl-3-methylimidazole-2-thione (HMImT), a low-viscosity extractant, was firstly synthesized and used to extract rhodium(i ). The negligible solubility of HMImT in solution was measured by HPLC to be about 0.015%. In the extraction process, rhodium(iii ) in solution was activated into rhodium(i ) by SnCl2 to improve extraction percentage, which was confirmed by XPS spectra. Under optimum conditions, the extraction percentage reached 99.6%. The neutral complexing mechanism was confirmed by UV-vis spectra, 1 H NMR spectra, titration method and FT-IR spectra. Quantum chemical calculations based on density functional theory (DFT) were also performed to support the results from a theoretical perspective. The extraction process was modeled by Langmuir ( R 2 = 0.998), Freundlich ( R 2 = 0.972) and Dubinin–Radushkevich isotherms ( R 2 = 0.990). According to the model results, the monolayer absorption capacity was 2.82 mmol g −1, and the mean free energy was obtained as 9.8 kJ mol −1 . The thermodynamic parameters of Δ G, Δ H and Δ S showed that the extraction process was spontaneous and exothermic. Pseudo-second-order kinetics well fitted the experimental data ( R 2 = 0.996). In addition, HMImT possesses high selectivity to Rh(i ) rather than other base metals during extraction. In summary, HMImT with low dissipation, excellent extractability and high selectivity for rhodium(i ) extraction will hold great promise and potential in the separation field.